2019
DOI: 10.1021/acssuschemeng.8b05480
|View full text |Cite
|
Sign up to set email alerts
|

Microporous Metal–Organic Framework with Dual Functionalities for Efficient Separation of Acetylene from Light Hydrocarbon Mixtures

Abstract: Separating acetylene from light hydrocarbon mixtures like ethylene is a very important process for downstream industrial applications. Herein, we report a new MOF [CuL 2 (SiF 6 )] (UTSA-220, L = (1E,2E)-1,2-bis(pyridin-4ylmethylene)hydrazine) with dual functionalities featuring optimal pore size with strong binding sites for acetylene. UTSA-220 exhibits apparently higher uptake capacity for C 2 H 2 than those for other light hydrocarbons. The potential of this material for trace C 2 H 2 removal from C 2 H 4 ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 51 publications
0
43
0
Order By: Relevance
“…Thus, we want to study MOF which has abundant bases and micropores. Moreover, in recent years, it has been shown that the establishment for the porous MOFs with bifunctional ligands is a feasible way to obtain the donor positions discordant MOFs [20][21][22]. In this research, a novel MOF containing Co(II) ions as nodes f[Co(L)]Á4H 2 OÁ2CH 3 CNg n (1) have been prepared via Co(NO 3 ) 2 Á6H 2 O reacting with the bifunctional ligand 5-(3,5-di-pyridin-4-yl- [1,2,4]triazol-1-ylmethyl)-isophthalic acid (H 2 L) under the solvothermal conditions (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we want to study MOF which has abundant bases and micropores. Moreover, in recent years, it has been shown that the establishment for the porous MOFs with bifunctional ligands is a feasible way to obtain the donor positions discordant MOFs [20][21][22]. In this research, a novel MOF containing Co(II) ions as nodes f[Co(L)]Á4H 2 OÁ2CH 3 CNg n (1) have been prepared via Co(NO 3 ) 2 Á6H 2 O reacting with the bifunctional ligand 5-(3,5-di-pyridin-4-yl- [1,2,4]triazol-1-ylmethyl)-isophthalic acid (H 2 L) under the solvothermal conditions (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the single-component adsorption-desorption isotherms for C 2 H 2 , CO 2 , and CH 4 were collected at three different temperatures of 278 K, 288 K, and 298 K and pressures up to 1 atm (Figure 3). The adsorption branches were overlapped with the desorption ones for all isotherms, indicating the ad- , [12] MOF-5 (26 cm 3 (STP) g -1 ), [12] BSF-1 (52.6 cm 3 (STP) g -1 ), [13] [Zn 12 (tdc) 6 (glycerol) 6 (dabco) 3 ] (55.1 cm 3 (STP) g -1 ), [14] UTSA-36 (56.8 cm 3 (STP) g -1 ), [15] Cu 2 (bdc) 2 (dabco) (60 cm 3 (STP) g -1 ), [16] Mg(HCOO) 2 (66 cm 3 (STP) g -1 ), [17] (Me 2 NH 2 ) 2 [Zn 6 (TBAPy) 2 (Ade-NH 2 ) 4 (μ 4 -O)] (69.4 cm 3 (STP) g -1 ), [18] CPL-2 (70 cm 3 (STP) g -1 ), [19] SIFSIX-3-Ni (74 cm 3 (STP) g -1 ), [6] UTSA-220 (76 cm 3 (STP) g -1 ), [20] Ni-gallate (80.4 cm 3 (STP) g -1 ), [21] and TIFSIX-2-Cu-i (91.8 cm 3 (STP g -1 ). [6] To our delight, ZJNU-8 adsorbed much more amount of C 2 H 2 than CO 2 and CH 4 especially at the low pressure.…”
Section: Resultsmentioning
confidence: 99%
“…And partial hydrogenation of acetylene into ethylene over catalyst 10 or solvent extraction of cracked olefins 11 are also involved with the purification of ethylene from acetylene. Adsorptive separation by porous materials is an alternative technology, especially, some metal-organic frameworks (MOFs) [12][13][14][15][16][17][18][19][20][21] with high volume, designable pore characteristics, and countless structural possibilities, can be employed into the gas separation processes, the adsorption selectivity and capacity are higher than the results of conventional adsorbents [22][23][24] such as zeolites and carbon-based, especially the adsorption and separation for C 2 H 6 /C 2 H 4 8,22,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] .…”
mentioning
confidence: 99%